Meconium aspiration syndrome: clinical profile, risk factors and outcome in central India - Kamble, Milind B.; Jain, Poonam (International Journal of Contemporary Pediatrics, 2018)
Background: Meconium aspiration syndrome (MAS) is a life-threatening respiratory disease affecting some neonates born through meconium-stained amniotic fluid (MSAF). MSAF complicates delivery in approximately 8% to 25% of live births, of which nearly 5% of the neonates born through MSAF develop MAS. The present study was undertaken to find out the prevalence of MSAF and MAS and to study the etiology, risk factors, clinical profile and outcome of MAS. Methods: By purposive sampling technique, all newborns, fulfilling the inclusion criteria during one year of study period were enrolled in this hospital based cross-sectional observational study. Risk factors and clinical profile were compared between those who died and survived. Results: Out of 8765 deliveries in hospital 1220 neonates were born with MSAF of which 94 neonates had MAS. Thereby, incidence of MSAF was 13.9% and incidence of MAS out of MSAF was 7.7 %. Of the 94 neonates who had MAS 13.82% died. Almost 3/4th of the MAS neonates were term and AGA. MAS were more common in primigravida mother (68%) and LSCS deliveries (53.2%). Of the total MAS 54.2% had thick meconium in whom mortality was 92.3%. The mortality in MAS cases was significant in low 5-minute APGAR score and non-vigorous baby. Conclusions: Since MSAF is associated with higher morbidity and mortality, if the knowledge of risk factors is known to health care personnel then timely referral or intervention can help in decreasing MAS and its complications.